2015
DOI: 10.3390/molecules20058429
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Catalytic Oxidation System: FePcOTf/H2O2 Applied for Cyclohexene Dihydroxylation

Abstract: Iron (III) phthalocyanine complexes were employed for the first time as a mild and efficient Lewis acid catalyst in the selective oxidation of cyclohexene to cyclohexane-1,2-diol. It was found that the catalyst FePcOTf shown excellent conversion and moderate selectivity relative to other iron (III) phthalocyanine complexes. The optimum conditions of the oxidation reaction catalyzed by FePcOTf/H2O2 have been researched in this paper. Iron (III) phthalocyanine triflate (1 mol %) as catalyst, hydrogen peroxide as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…As a result, recent decade witnesses a great number of reports about MPc especially their applications as catalysts. Fe(II)-Pc is an active MPc that was employed in the oxidation of wide variety of organic substrates including β -isophorone 4 , catechol 5 , starch 6 , aromatic pollutant 7 , cyclohexene 8 , cyclohexane 9 , alcohols 10 , and methane 11 . The high activity of this catalyst is attributed to the large number of π electrons which are easily transported between the catalyst and substrate, similar to its analogue, Fe(II)-porphyrin 12 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, recent decade witnesses a great number of reports about MPc especially their applications as catalysts. Fe(II)-Pc is an active MPc that was employed in the oxidation of wide variety of organic substrates including β -isophorone 4 , catechol 5 , starch 6 , aromatic pollutant 7 , cyclohexene 8 , cyclohexane 9 , alcohols 10 , and methane 11 . The high activity of this catalyst is attributed to the large number of π electrons which are easily transported between the catalyst and substrate, similar to its analogue, Fe(II)-porphyrin 12 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this obstacle, organic initiators (generally peroxides, peracids, diazo-compounds, etc. ) , and/or promoters (e.g., aliphatic aldehydes) are usually explored. , According to the mechanism, the enlisted compounds speed up the oxidation using the free radicals generated in the course of their homolysis. In a similar, although not identical, manner, N -hydroxyphthalimide (NHPI) , enables to transfer electrons by the way of mimicking biological oxidation. , …”
Section: Introductionmentioning
confidence: 99%
“…10 To overcome this obstacle, organic initiators (generally peroxides, peracids, diazo-compounds, etc.) 12,13 and/or promoters (e.g., aliphatic aldehydes) are usually explored. 14,15 According to the mechanism, the enlisted compounds speed up the oxidation using the free radicals generated in the course of their homolysis.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the catalyst FePcOTf shows excellent conversion and moderate selectivity relative to other iron(III) phthalocyanine complexes. 187 Simple Fe(NO 3 ) 3 •9H 2 O was demonstrated to be able to catalyze the oxidation of monoterpenes by hydrogen peroxide in methanol. In these reactions, α-and β-pinene were preferentially oxidized to allylic ethers (i.e., myrtenol methyl ether).…”
Section: Epoxidationmentioning
confidence: 99%